The Delay of the Punitive Lawsuit in the Investigation stage A study of the Iraq laws (Al-Mansour Journal, 2022)
Abstract      The objective of the legislator of the punitive lawsuit is to maintain security and peace of the individual and the society, and to assertright and justice. Through this they can afflict punishment against the breaches of the security and safety which is cannot be achieved without the completion of investigation according to the plan drawn to know the doer and to reveal the truth. In front of that the progress of investigations may reveal many of the objective and formal obstacles which might delay the conclusion of the punitive lawsuit. All that is dealt with in the research that includes two inquiries; the first is about the meaning of investigations and its authority. In the second inquiry we discussed the delay of investigatory procedures which is subdivided into two sections. The researcher is concluded with the Conclusion that includes the most important findings.